The spread of existing diurnal squirrels across the Bering and Panamanian land bridges. American Museum novitates - Moore, Joseph Curtis. (New York, N.Y. : American Museum of Natural History, 1961)
26 p. : maps 24 cm. Includes bibliographical references (p. 24-26). "There are four living phyla of diurnal squirrels with taxa on opposite sides of Bering Strait which are differentiated to a degree that is recognized to be of less than generic rank. For each of these four phyla the greatest range of a single species occupies the principal continuous land mass west of the Strait. Also, for each phylum a greater number of species occurs on the east than on the west. It is suggested that, other things being equal, a species that occupies the large Palearctic range is the dominant species in its phylum, and, when ecological conditions are suitable for a spread across the Bering land bridge, it would be the dominant species that would spread. Some of the more numerous Nearctic species are considered to have evolved from the populations that spread from west to east and then to have become geographically isolated. The Palearctic Region is regarded therefore as the center of dispersal for these diurnal squirrel phyla: the subtribes Sciurina, Tamiina, Spermophilina, and Marmotina. The probable place of origin is shown to be the Nearctic Region for the Tamiina, the Spermophilina, and the Marmotina. The large, relatively unbroken area of the northern Palearctic Region is, and may for a long time have been, the largest area available in the world as a range for a single species of terrestrial vertebrates, and the possibility is noted that it may be the area on which the dominant species are evolved in vertebrate phyla other than diurnal squirrels. If such is the case, the above-described mechanism may be conceded to have contributed importantly to the predominantly eastward spreading across the Bering land bridge recognized by Simpson (1947) and Darlington (1957). Central America, or parts of it, as an island or archipelago must have served as a staging area for the adaptation of squirrel species of Nearctic origin to tropical conditions over perhaps a substantial portion of the Pliocene before the emergence of a ...